The Association between Sleep and Depression during Late Pregnancy and the Early Postpartum Period - Jones, Angela G.; Hadaie, Bachar S.; Bennett, Rachel; Kumar, Nimisha; Saha, Chandan K.; Haas, David M. (American Journal of Perinatology Reports, 2024)
Objective To assess and correlate sleep quality and depressed mood symptoms in the late pregnancy and early postpartum periods.Study Design In a prospective pilot observational study, participants completed the Pittsburgh Sleep Quality Index (PSQI) and the Edinburgh Postnatal Depression Scale (EPDS) questionnaires at delivery, 1, and 2 months postpartum. Pearson's correlation coefficients and PROC MIXED function estimated overall correlation for repeated measures.Results Twenty-six women were enrolled with a mean gestational age at delivery of 38.4 (± 2.4) weeks. Sleep quality and mood data were available at the three time points for 24, 16, and 11 participants, respectively. Poor sleep scores were noted by 75.0, 87.5, and 72.7% of women at the three time points. An elevated EPDS score of 10 or higher was claimed by 20.8, 12.5, and 18.2% of women, respectively. Higher PSQI scores were positively associated with higher EPDS scores overall (r = 0.71, p < 0.001) and at each of the individual time points (r = 0.79, p < 0.0001; r = 0.52, p = 0.04; and r = 0.70, p = 0.016, respectively). None of the women reporting good sleep quality had elevated EPDS scores.Conclusion Poor sleep is commonly reported around delivery, and at 1 and 2 months postpartum, and there is an association between poor sleep and depression symptoms.
Keywords: pregnancy; sleep; depression; postpartum; postpartum depression